Glandular Odontogenic Cyst in the Anterior Mandible: A Case Report of a Conservative Approach and a Recurrence Detection - Wladimir Gushiken de Campos; Rita Araújo; Victor Martin; Marília Trierveiler; Pedro Gomes; Celso Augusto Lemos (Diagnostics, 2023)
Purpose: The glandular odontogenic cyst (GOC) is considered a rare developmental cyst, with an odontogenic origin and both epithelial and glandular characteristics, with less than 200 reported cases in the literature. Methods: In the present case, a 29-year-old man was referred for evaluation of an asymptomatic slow-growing swelling in the anterior region of the mandible, with one-year history. The patient’s medical history did not reveal any systemic alteration. The extraoral examination did not show enlargement of the facial contour and the intraoral examination showed vestibular and lingual swelling. Panoramic radiography and CT scan revealed a well-defined unilocular radiolucent lesion involving the inferior incisors and canines bilaterally. Results: Histopathological analysis revealed multiple cysts lined by stratified epithelium with varying thickness and characteristics, in addition to duct-like structures filled with PAS-positive amorphous material, suggestive of GOC. Conservative treatment was performed through surgical curettage, peripheral ostectomy of the surgical site and apicectomy of the teeth involved in the lesion. There was one recurrence, which was detected in postoperative follow-up, leading to a new surgical approach. Conclusions: Fifteen months after the second procedure, no signs of recurrence were identified, and bone neoformation within the surgical site occurred, supporting that a conservative approach for the treatment of GOC is viable.